Strategi Politik Pasangan Calon Lucky dan Syaefudin dalam Pemilihan Kepala Daerah Serentak di Kabupaten Indramayu Tahun 2024 - Fadilah, Nur; Ismanudin; Ibrahim (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This research is entitled “The Political Strategy of the Candidate Pair Lucky Hakim and Syaefudin in the 2024 Simultaneous Regional Election in Indramayu Regency.” The purpose of this study is to identify and analyze the political strategies employed by Lucky Hakim and Syaefudin in winning the 2024 regional election, as well as to determine the supporting and inhibiting factors that influenced their political communication process during the campaign. This research applies Peter Schroder’s theory of political strategy as the analytical framework and uses a qualitative research method. Data were collected through documentation studies and in-depth interviews. The findings reveal that the political strategy implemented by Lucky Hakim and Syaefudin focused on a direct approach to the community through blusukan or door-to-door visits across village areas. This approach effectively built emotional closeness and strengthened public trust toward the candidate pair. Furthermore, Lucky Hakim’s high popularity and electability served as significant social capital that attracted strong public enthusiasm, particularly among grassroots groups such as housewives. Survey data indicated that Lucky Hakim’s personal image and popularity played a crucial role in supporting the pair’s victory. In addition, the success of this political strategy was also supported by the significant contribution of the campaign team and a wide network of volunteers. These volunteers actively expanded the campaign’s reach, organized political activities at the local level, and maintained political consolidation until the voting stage. Therefore, the victory of Lucky Hakim and Syaefudin resulted from the synergy between direct communication strategies, personal image strength, and the effective mobilization of volunteers in building broad public support across Indramayu Regency.